Attack on Titan. Before the fall. 4 - Isayama, Hajime, 1986-; Suzukaze, Ryo (Before the fall, 2015)
"After escaping what should have been certain death and defeating a Titan outside the walls, Kuklo and the Survey Corps make it back to the safety of Shiganshina, where the Military Police are waiting to arrest him for the murder of his former master Dario. But there will be no trial and no execution for the Titan's son. The MPs have a much crueler punishment in mind..."--P. [4] of cover.